Título Padrão: O Oceano Antártico: nossa melhor oportunidade? - Isla, Enrique (Arquivos de Ciências do Mar, 2022)
The Southern Ocean has a significant importance in global climate regulation because its great potential to sequester atmospheric carbon and its enormous contribution to the transport of heat and mass in the global ocean. Antarctic benthos presents unique characteristics developed after millions of years of evolution and greatly contribute to the maintenance of the global biodiversity and genetic pool. Ongoing anthropogenic pressure seriously threaten Southern Ocean’s current characteristics and the ecosystems services they provide. In my opinion, individual actions toward environmental protection emerges as the fastest alternative to ameliorate the current situation. Keywords: Antarctica, climate change, anthropogenic impacts, social behavior.